The role of 3D-printing technology in the diagnosis of Eagle syndrome: A case report. Issue 13 (March 2018) - Lee, Dong Hoon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract: Rationale: Eagle syndrome is a rare clinical condition that can be associated with elongation of the styloid process. Patient concern: A 55-year-old man was presented with vague throat discomfort for several years. Diagnosis: 3-dimentional (3D) computed tomography (CT) reconstruction, and printing revealed bilateral elongated styloid processes. Interventions: The patient has been treated medically, and continues to demonstrate improvement with conservative treatment for 2 years. Outcome: We report usefulness of 3D CT and 3D printing technology for diagnosis of Eagle syndrome. Lessons: 3D CT reconstruction, and printing are beneficial in determining appropriate surgical strategy, and allowing the physician to better explain the lesion, and surgical details to patients.